New Hesperiidae additions to the Papilionoidea fauna of Uttar Pradesh, India (Insecta: Lepidoptera) - Brij Lal; Rupak De; Ratindra Pandey; Abu Arshad Khan; Lalit Kumar Verma; Taslima Sheikh (SHILAP, 2025)
This research article unveils significant additions to the Papilionoidea fauna of Uttar Pradesh, India. Through meticulous observation and documentation, two species belonging to the Hesperiidae family were discovered within the region. The first species, Caprona ransonnettii (Felder, 1868), and the second, Burara oedipodea (Swainson, 1820), were identified and recorded as novel findings in the area. These discoveries were made through comprehensive field surveys, which included systematic observations and detailed recording of butterfly species in various habitats over an extended period. Such findings contribute valuable insights into the biodiversity of Uttar Pradesh’s Papilionoidea fauna. The study sheds light on the distribution and presence of these species, enhancing our understanding of the ecological dynamics within the region. These results underscore the importance of continued research and conservation efforts to preserve the rich diversity of Papilionoidea species in Uttar Pradesh, India.